Utilization of the "Connecting the Dots" Worksheet to Engage Undergraduate Students in Health Promotion Program Planning - Raymona Lawrence; Ashley Walker (Georgia Southern University, 2017)
Background: Developing a health promotion program plan requires attention to the links between objectives, activities, and overall program goals. Instructors developed the "Connecting the Dots" worksheet to help students establish these linkages. Methods: The "Connecting the Dots" worksheet included six questions pertinent to the students' health promotion program plans. The worksheet was given to the students in a flipped classroom setting. Evaluation of the effectiveness of the tool was based upon group presentations at the end of the semester. Results: Students developed more viable program plans that included stronger links between objectives and corresponding program activities. Conclusions: The "Connecting the Dots" worksheet is a promising tool for engaging public health students in the process of developing health promotion program plans. Key words: Health promotion program planning, public health, pedagogy